ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS DITINJAU DARI KEPERCAYAAN DIRI SISWA SMP KELAS VIII DI KOTA CIMAHI PADA MATERI BANGUN DATAR SEGI EMPAT - Keni Eviliasani; Heris Hendriana; Eka Senjayawati (IKIP Siliwangi, 2018)
This study aims to analyze the ability of mathematical creative thinking regarding student self-confidence in learning mathematics on the matter of building a rectangular flat. In this study using a descriptive method with the qualitative approach by analyzing the level of mathematical creative thinking seen from the level of student confidence. The population of this research is 30 students of class VIII in Senior High School of 3 Cimahi academic year 2017-2018. The results of this study show that students who have high self-esteem (KDT) will have a high creative thinking ability, students who have moderate confidence (KDS) will have the ability to think creatively that, as well as students who have low self-confidence will have low creative thinking ability.